The Politics of Dementia - Krüger-Fürhoff, Irmela Marei; Schmidt, Nina; Vice, Sue (Media and Cultural Memory / Medien und kulturelle Erinnerung, 2021)
This edited volume analyses how forms of individual and societal forgetting, as envisaged in contemporary literary texts and other works of art, tie into cultural concepts of pathological memory loss how globally diverse experiences of violence and trauma are represented as relating to dementia and in what ways this affects our understanding of the fraught and entangled histories of the twentieth and twenty-first centuries.